(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Respiratory diseases in early childhood represent a significant concern in pediatric healthcare due to their high incidence and recurrent nature. Acute obstructive bronchitis and bronchiolitis are among the most severe forms, often requiring hospitalization and prolonged recovery. Although pharmacological advancements have been made, there remains a lack of pathogenetically justified treatments, particularly concerning the use of immunomodulatory drugs like immunomodulin in early-age patients. This study aimed to evaluate the clinical efficacy of incorporating immunomodulin into the therapeutic regimen of children under three years with acute obstructive bronchitis and bronchiolitis. A comparative clinical observation was conducted involving traditional treatment groups and those receiving immunomodulin, assessing respiratory and intoxication symptom resolution timelines. The inclusion of immunomodulin significantly reduced the time required for symptom relief, including dyspnea, cyanosis, tachycardia, cough, and auscultatory wheezing, compared to traditional therapy alone (p<0.05). The study presents new empirical evidence on the added value of immunomodulin in accelerating recovery in obstructive pulmonary infections in early childhood a domain previously underexplored. Integrating immunomodulin into conventional pediatric treatment protocols may improve outcomes, reduce hospital stays, and contribute to individualized therapy in respiratory pathologies of early childhood.